External Constraints on Sustainable Growth in Transition Countries - Kazimierz Laski (The Vienna Institute for International Economic Studies (wiiw), 2001)
Sustainable growth in catching-up countries requires the widening of the foreign trade bottleneck. It is however not clear whether two prescriptions aiming at solving this problem greater exchange rate flexibility and the liberalization of the capital market, are in reality not contradictory. The theoretical background is supplied by two papers of A. Bhaduri. In 'On the viability of external debt' the relation between the rate of growth and the rate of interest as well as the relation between the propensities to export and to import are analysed. In 'Capital flows, the balance of payments and the exchange rate', the model proving the extreme fragility of the prevailing system is demonstrated. The experience of Latin American economies is analysed by J. López-Gallardo. He examines the advantages and disadvantages of the modernization strategy based on the liberalization of foreign trade and of the capital market. His main conclusion is that the current account deficits and financial crises were not provoked by insufficient private savings and not even by insufficient investment, but mainly by a premature opening of the economy and lack of an industrial policy. These conclusions are confronted with the experience of CEECs, mainly Poland, in the papers of L. Podkaminer. He introduces the novel concept of import-led growth and concentrates on causes and consequences of currency appreciation in these countries. The first repercussions of FDI inflows on the current account in the CEECs are analysed in the paper of G. Hunya and S. Richter.
Keywords: F21; F31; F32; F34; 330; external debt; FDI; trade and current account balances; exchange rate regimes; fiscal and monetary policy; CEECs